Prevalence and risk factors of axial neck pain in patients undergoing multilevel anterior cervical decompression with fusion surgery - Sen Liu; Da-Long Yang; Ruo-Yu Zhao; Si-Dong Yang; Lei Ma; Hui Wang; Wen-Yuan Ding (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Objectives The aim of this study was to explore the prevalence and risk factors for axial neck pain in patients undergoing multilevel anterior cervical decompression with fusion surgery. Methods In this study, 88 patients, who underwent multilevel anterior cervical decompression with fusion surgery from January 2012 to January 2017, were retrospectively reviewed. Based on the postoperative axial neck pain, the patients were classified into two groups: axial pain group and no axial pain group. The patients were followed up 3 weeks, 3 months, and 1 year after cervical anterior surgery for the early- and long-term clinical evaluation. The possible effect factors included demographic variables (age, sex, BMI, smoking, drinking, heart disease, hypertension, diabetes, preoperative kyphosis, preoperative axial neck pain, preoperative JOA scores, and ODI) and surgery-related variables (surgical option, vertebral lesions, spinal canal stenosis rate, superior fusion segment, presence of intramedullary high signal intensity). Results The prevalence of axial neck pain was 27.3% (24 cases of 88). Our results showed that preoperative axial neck pain (62% vs 23%, P < 0.001) and preoperative kyphosis (42% vs 21.9%, P < 0.001) were risk factors for axial pain after multilevel anterior cervical surgery. Additionally, for patients with preoperative cervical kyphosis, compared to no axial pain group, the axial neck group was significantly more likely to exist a higher preoperative angle of C2–7 (13.31 ± 2.33 vs 7.33 ± 2.56, P < 0.001) and a higher correction range for kyphosis (20.24 ± 4.12 vs 12.34 ± 3.12, P < 0.001). However, for all the patients with postoperative axial symptoms, the improvement rate of axial pain was significantly higher for patients without cervical kyphosis at the early-term follow-up (3 weeks) (P = 0.032), no significant differences were found at the medium-term (P = 0.554) and long-term follow-up (P = 0.902), and improvements of clinical symptom have no obvious difference at the last follow-up. Conclusions Overall, preoperative axial neck pain and kyphosis could predict axial neck pain for patients undergoing multilevel anterior cervical decompression with fusion surgery, and recovery of cervical kyphosis may contribute to the long-term recovery of neural function, but may also suffer from risk of short-term axial pain, which could be reduced through moderate cervical curvature recovery.